2015
DOI: 10.1063/1.4928587
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diffusivity anisotropy measured by a temperature wave method in the homologous series of (p-alkoxybenzylidene)-p′-octylaniline (nO.8)

Abstract: The anisotropy of thermal diffusivity in four homologues of (p-alkoxybenzylidene)-p'-octylaniline (nO.8, n = 4 - 7) was measured using a temperature wave method. The results show that the thermal diffusivity component along the director (α(∥)) is considerably larger than that perpendicular to the director (α(⊥)) in all mesophases, i.e., nematic (N), smectic A (SmA), smectic B (SmB), and smectic G (SmG) phases. Both components of the thermal diffusivity show a dip at the second- or weakly first-order N-SmA phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Abundant research work has been carried out to understand the thermoelastic anisotropy of LCs and how it is related to the molecular structure. For mechanical anisotropy, it is generally accepted that (1) the elastic constants ( C ) are higher along (∥) the director than perpendicular (⊥) to it, (2) the elastic anisotropies, ( C ∥ – C ⊥ )/ C ⊥ , is on the order of a few percent or less, and (3) the dimensional ratio of rigid cores and side chains determines the elastic anisotropy. For thermal anisotropy, it has been shown that (1) the thermal diffusivity (α) is higher along the director than perpendicular to it, (2) the thermal anisotropy, (α ∥ – α ⊥ )/α ⊥ , could reach 100% or even more, and (3) the thermal anisotropy stems from structural anisotropy of the LC molecules, and is not dependent on the long-range layer ordering of the LC molecules. However, previous research typically focused on either the mechanical or the thermal properties in 1–2 phases of the LCs. To the best of our knowledge, no combined study of the anisotropic mechanical and thermal properties of LCs over a wide range of temperatures has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant research work has been carried out to understand the thermoelastic anisotropy of LCs and how it is related to the molecular structure. For mechanical anisotropy, it is generally accepted that (1) the elastic constants ( C ) are higher along (∥) the director than perpendicular (⊥) to it, (2) the elastic anisotropies, ( C ∥ – C ⊥ )/ C ⊥ , is on the order of a few percent or less, and (3) the dimensional ratio of rigid cores and side chains determines the elastic anisotropy. For thermal anisotropy, it has been shown that (1) the thermal diffusivity (α) is higher along the director than perpendicular to it, (2) the thermal anisotropy, (α ∥ – α ⊥ )/α ⊥ , could reach 100% or even more, and (3) the thermal anisotropy stems from structural anisotropy of the LC molecules, and is not dependent on the long-range layer ordering of the LC molecules. However, previous research typically focused on either the mechanical or the thermal properties in 1–2 phases of the LCs. To the best of our knowledge, no combined study of the anisotropic mechanical and thermal properties of LCs over a wide range of temperatures has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, α // is 2.9 times greater than α ⊥ . This anisotropy is comparable to that of monomeric LCs, but the magnitude of α is more than twice that of monomeric LCs. , Both the anisotropy and magnitude of α are comparable to those of another side-chain LCs, P m BE1, polymethacrylates bearing a different mesogenic moiety of methoxyphenyl benzoate …”
Section: Resultsmentioning
confidence: 64%
“…This anisotropy is comparable to that of monomeric LCs, but the magnitude of α is more than twice that of monomeric LCs. 11,12 Both the anisotropy and magnitude of α are comparable to those of another side-chain LCs, PmBE1, polymethacrylates bearing a different mesogenic moiety of methoxyphenyl benzoate. 13 The α // and α ⊥ values for PMnMA are listed in the sixth and seventh rows of Table 2, respectively.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal diffusivity and TC in LC phases are known to be larger in the direction parallel to the nematic director than perpendicular thereto. Thermal anisotropy has been studied both experimentally and computationally by using the Gay–Berne model. In experimental studies, Urbach et al discussed the thermal diffusivity behavior by employing a kinetic model based on an extension of the Eyring theory to anisotropic fluids . On the other hand, Sarman Laaksonen calculated the TC of LC phases of the Gay–Berne fluid and suggested that the anisotropy is derived from molecular movement because the movement along the direction perpendicular to the director is impeded by side-by-side collisions .…”
Section: Introductionmentioning
confidence: 99%